ANALISIS EFEKTIVITAS BIAYA PENGOBATAN HIPERTENSI PADA PASIEN RAWAT JALAN DI KLINIK NURUL HASANAH TAHUN 2022 - Akbar, Depy Oktapian; Yaumil, Fairuz; Apdillah Setiawan, Aldi (Jurnal Insan Farmasi Indonesia, 2023)
Hypertension or high blood pressure is a serious medical condition that significantly increases the risk of heart, brain, kidney and other diseases. Prevalence of the population with high blood pressure is 34.11%. The aim of this research is to determine the cost effectiveness between the use of the antihypertensive drugs amlodipine and candesartan in BPJS outpatient hypertension patients at the Nurul Hasanah Kapuas Clinic in 2022. This research uses the CEA pharmacoeconomic method based on the direct medical cost perspective used, namely health service cost data. The results obtained from this research are that amlodipine therapy is more cost effective than candesartan with an Average Cost Effectiveness Ratio (ACER) value for amlodipine of Rp. 156,441.92 and candesartan Rp. 166,527.78.